Dopaminergic and Clinical Correlates of Pathological Gambling in Parkinson’s Disease: A Case Report - Callesen, Mette B.; Hansen, Kim V.; Gjedde, Albert; Linnet, Jakob; Møller, Arne (Frontiers in Behavioral Neuroscience, 2013)
Dopaminergic medication for motor symptoms in Parkinson’s disease recently has been linked with impulse control disorders, including pathological gambling, which affects up to 8% of patients. Pathological gambling often is considered a behavioral addiction associated with disinhibition, risky decision-making, and altered striatal dopaminergic neurotransmission. Using [11C]raclopride with positron emission tomography, we assessed dopaminergic neurotransmission during Iowa Gambling Task performance. Here we present data from a single patient with Parkinson’s disease and concomitant pathological gambling. We noted a marked decrease in [11C]raclopride binding in the left ventral striatum upon gambling, indicating a gambling-induced dopamine release. The results imply that pathological gambling in Parkinson’s disease is associated with a high dose of dopaminergic medication, pronounced motor symptomatology, young age at disease onset, high propensity for sensation seeking, and risky decision-making. Overall, the findings are consistent with the hypothesis of medication-related pathological gambling in Parkinson’s disease and underscore the importance of taking clinical variables, such as age and personality, into account when patients with Parkinson’s disease are medicated, to reduce the risk of pathological gambling.